Assessment and Solutions to Food Waste at Congress Events: A Perspective of the MagNuS Project - Fernández-Zamudio, María A.; Zarzo, Inmaculada; Pina, Tatiana; Soriano, José M.; San Onofre, Nadia (MDPI, 2024)
Addressing global food waste is a formidable challenge, requiring comprehensive efforts across the food supply chain, particularly in sectors prone to waste like HoReCa (Hotel, Restaurant, and Catering). In MICE (Meetings, Incentives, Conventions, and Exhibitions) tourism, where gastronomy is a major attraction, overlooked meal services during working meetings contribute significantly to food waste. The MagNuS (Magnitude, Nutritional value, and Sustainability) project aims to assess and address food waste during conference events at the Valencia Conference Center in Spain. This study quantifies waste, categorizes it by food groups, estimates the potential number of individuals that could be fed with discarded food, and assesses energy and nutritional values. Across three events, 104.4 kg of food waste was documented, with cereals having the highest wastage, followed by legumes, fish, and others. Acknowledging potential underestimation due to reliance on cooked values, this study suggests using residues for vermicomposting or composting as sustainable waste management alternatives. These findings have implications for future initiatives, advocating diverse strategies to minimize food waste during congress events, aligning with the Sustainable Development Goals. The MagNuS project contributes valuable insights to sustainable practices in MICE tourism, informing policies and operational decisions to reduce the environmental impact of food waste.